(untitled) (Palíndromo, 2021)
We propose in the article the alignment of rhizome concept of Deleuze & Guattari’s to photogra- phy, understanding it as a possible cultural artifact for cultural studies. Rhizomatic photography is presented as an articulator of history, culture and memory.